The Phytochemistry and Antioxidant Activity of the Nelumbo nucifera (Lotus) Plant: A Review: Ubeysinghe S.W.A.N.S.1* and De Silva H.I.C.1 (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2022)
Plant extracts are used in a range of products, including fairness creams, fragrances, body lotions, and other formulations. Herbal plants comprise alkaloids, glycosides, terpenes, steroids, flavonoids, tannins, and other secondary metabolites. Polyphenols have antioxidant properties, which have an assortment of health benefits. Medicinal properties can be found in almost all parts of the Nelumbo nucifera (Lotus) plant. Phytochemicals, as well as secondary metabolites like phenols, flavonoids, tannins, alkaloids, sterols, terpenoids, cardiac glycosides, coumarins, and quinones, are found in the lotus extracts. Methanol and Butanol extracts of N. nucifera are observed to have scavenging activities on free radicals and hydroxyl radicals, as well as the metal-binding ability and reducing power. Natural antioxidant potential has been observed in the leaf, stamens, and seed extracts of N. nucifera. The antioxidant activities of various organic and aqueous extracts of N. nucifera have been demonstrated in pharmacological studies. Antioxidant activity and total phenolic content may differ depending on geographical location and growth conditions of the plant. Further research into the fine structures of lotus active ingredients, as well as structure-activity relationship mechanisms, are required in the future to overcome the challenges of different extraction methods and in the studies of therapeutic efficacy of the Nelumbo nucifera plant. Keywords: Nelumbo nucifera, Phytochemistry, Antioxidant property, DPPH, Lotus extract, free radicals